Screening and enzymatic activity of high-efficiency gellan lyase producing bacteria Pseudoalteromonas hodoensis PE1. Issue 1 (1st January 2019) - Li, Ang; Luo, Hangqi; Hu, Tingting; Huang, Jingyu; Alam, Nafee-Ul; Meng, Yuan; Meng, Fenbin; Korkor, Nartey Linda; Hu, Xiufang; Li, Ou
ABSTRACT: Gellan is a widely used microbial polysaccharide and one of the more effective ways to expand its application value would be to investigate the mechanism of gellan lyase and to produce gellan oligosaccharide. In this study, efficient gellan degrading bacteria were screened. One of the strains with high efficient gellan degradation capacity was labeled PE1. Through physiological and biochemical analysis of 16S rDNA, the species was identified as Pseudoalteromonas hodoensis . The optimum conditions for enzymatic activity and how it was affected by metal ions were determined, and the results showed that the lyase activities were much higher than those of previously reported (about 20 times). The gellan degradation products were determined by thin-layer chromatography and the oligosaccharides were determined by high-efficiency liquid chromatography to analyze the action site of lyase. This study laid a solid foundation which elucidates the production and application of gellan oligosaccharides. Research highlights ● High efficiency gellan lyase producing bacteria ● Optimization of reaction conditions for gellan degradation ● Oligosaccharides were detected by TLC and HPLC to speculate the lyase action sites.